Assessing African Vultures as Biomonitors and Umbrella Species - Thompson, Lindy J.; Krüger, Sonja C.; Coverdale, Brent M.; Shaffer, L. Jen; Ottinger, Mary Ann; Davies, John P.; Daboné, Clément; Kibuule, Micheal; Cherkaoui, S. Imad; Garbett, Rebecca A.; Phipps, W. Louis; Buechley, Evan R.; et al. (Frontiers in Conservation Science, 2021)
African vulture populations are rapidly declining, yet funding and other resources available for their conservation are limited. Improving our understanding of which African vulture species could best serve as an umbrella species for the entire suite of African vultures could help conservationists save time, money, and resources by focusing their efforts on a single vulture species. Furthermore, improving our understanding of the suitability of African vultures as biomonitors for detecting environmental toxins could help conservation authorities to detect changes in ecosystem health. We used a systematic approach based on criteria selected a priori to objectively evaluate the potential of each of the 10 resident African vulture species as (i) an umbrella species for all of the African vulture species, and (ii) an avian biomonitor. For each criterion, we scored the respective African vulture species and summed the scores to determine which species was best suited as an umbrella species and as an avian biomonitor. Our results showed that, overall, certain aspects of vulture ecology (large population sizes, large body sizes, long lifespans, and their ability to be monitored over numerous seasons) support their suitability as biomonitors, while other ecological traits, including their diets and the public's perceptions of vultures, could diminish their suitability. The White-backed Vulture (Gyps africanus) was the best fit of the 10 vulture species in our assessment as both an avian biomonitor and an umbrella species for all African vulture species. Meanwhile, significant knowledge gaps for other species inhibit their utility as biomonitors. Due to their large home-range sizes, African vultures may only be useful as biomonitors at a regional scale. However, there could be value in using the White-backed Vulture as an umbrella species, as an aid to conserve the entire suite of African vulture species.